China's Arctic Ambitions and What They Mean for Canada (2018)
Science forms an important foundation for Canada’s Northern Strategy across all four of its pillars, a fact demonstrated by Canada’s world leading $150 million investment in the International Polar Year (2007–09). 2 Arcticresearch initiatives emphasize Canada’s international obligation to contribute to knowledge about the “nature, mechanisms and extent” of connectionsbetween the Arctic and the rest of the globe. The federal government is carrying through on its promise to create new research infrastructure, particularly a world class Canadian High Arctic Research Station (CHARS) in Cambridge Bay, Nunavut, and Canadian granting councils are encouraging researchers to coordinate their efforts across relevant topic areas (such as resource development, transportation, community sustainability, health, and the environment) so that they can translate their findings into concrete policy ecommendations.